Mahr Provisions and the Case for Shari’a Arbitration - Cora Allen (Washington University Law Review, 2018)
The global Muslim population is currently estimated at 1.8 billion people, comprising twenty-four percent of the total global population. The United States alone is home to 3.45 million Muslim individuals. Further, both global and national Muslim populations are predicted to grow rapidly over the next half-century. The Pew Research Foundation predicts that between 2015 and 2060, the global Muslim population will grow over twice as fast as the overall world population and that by 2050, the Muslim population in America will reach 8.1 million. These changes would make Muslims the second-largest religious group in the United States and the largest religious group in the world by the second half of this century. Yet, from a legal standpoint, American courts are still not familiar with many aspects of Islamic legal and cultural traditions. Nowhere is this more apparent than in the context of Islamic marriage. Marriage is a particularly complex area of family law because it is not singularly a civil matter, but instead a fusion of legal rules, religious practices, and socio-cultural expectations and norms. Judicial interpretations in United States courts of Islamic marriage contracts reflect this complexity. In particular, U.S. courts struggle to interpret provisions within Islamic marriage contracts, called mahr provisions, which regulate the division of property in the case of certain types of divorce. This confusion is due in large part to a misunderstanding of the context and function of the mahr, leading courts to either invalidate these provisions blanketly or otherwise improperly treat mahr agreements as prenuptial contracts. Another common issue presents itself when parties seek enforcement of a mahr agreement that was part of a divorce obtained outside of the United States, specifically when the divorce was achieved through the unilateral method of talaq. Cases demonstrate a multitude of court outcomes, often inconsistent with one another. What results is unreliable holdings, unclear precedent, a disregard for party intentions, and, ultimately, a perverse incentive for either husband or wife (and sometimes both) to seek opportunistic enrichment in a court with little knowledge of the cultural and religious context of these agreements. This Note suggests that the solution to this chaos is not simply to instruct American judges on the intricacies of Islamic law and marriages (although that certainly would not worsen the issue). Instead, a pluralist approach to Islamic marriages should be adopted, similar to the stance courts have taken on Jewish legal arbitration tribunals. Under this regime, Islamic arbitrators would serve as an alternative to civil courts in resolving conflicts involving mahr agreements, under the oversight of secular law. This approach would not only ensure protection of basic rights, but would also encourage self-regulation by the religious arbitral body to conform to fundamental civil family law principles of due process and equal protection. Finally, it would recognize and validate that there is more than one conception of marriage and divorce within American society.
Keywords: Mahr Provisions; Shari’a Arbitration; Islamic marriage; talaq; pluralism; Islamic arbitrators; mahr agreements; religious arbitral body; family law; Prenuptial Contracts; Vagueness; First Amendment; International Comity